Microwave characterization of rubber composites using rectangular dielectric waveguide (RDWG) / Kamariah Ismail, Zaiki Awang and Mazlena Esa - Ismail, Kamariah; Awang, Zaiki; Esa, Mazlena
This paper describes a non-destructive measurement system for microwave characterization of rubber composites using RDWG system at X-Band. The set-up is able to detect the various fillers and particle sizes of the fillers in rubber composites,